Case Study of Application of Higher Order Thinking Skill (Hots) Students in Faith Grade 5 and 6 Daniel Creative School Elementary Semarang School Year 2022-2023 - Titin Martanti (Jurnal Indonesia Sosial Teknologi, 2024)
This study aimed to determine the application of higher-order thinking Skills (HOTS) in Faith subjects for grade 5 and 6 students. This research uses qualitative research methods with a case study type of research, where data collection is carried out through structured interviews with grade 5 and 6 students at Daniel Creative School Semarang. Analysis and discussion of the research problem resulted in two findings. First, related to the HOTS learning process, it was found that the application of the concept was already running but still needed to be improved to suit the characteristics of students. Grade 5 students begin to cope with complex material, while grade 6 students still face obstacles in concentration and motivation. Second, HOTS learning outcomes show that students face difficulty answering questions, especially in Bible literacy analysis and literacy-based problem-solving. The questions require critical and creative thinking skills, but their application is still tricky